2021
DOI: 10.1016/s1473-3099(20)30636-8
|View full text |Cite
|
Sign up to set email alerts
|

Dental procedure aerosols and COVID-19

Abstract: e73providers to be compared with infection incidence in the community.To date there are no reported clusters of respiratory-transmitted diseases, including severe acute respiratory syndrome coronavirus and SARS-CoV-2, in dental providers or patients in a dental setting.We declare no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 5 publications
2
67
0
3
Order By: Relevance
“…Infectious droplets from saliva or blood may enter the aerosol and expose the dental team to an increased risk of infection though direct inhalation, contact with eyes and contact with contaminated work surfaces. 6,7 Dental aerosols therefore have the potential to provide a path for the transmission of COVID-19, 8,9 which may remain infectious for between two hours to nine days in a humid environment. 7 Research on the influenza virus has also demonstrated that the total viral copies are 8.8 times more numerous in particles <5 μm than in particles ≥5 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Infectious droplets from saliva or blood may enter the aerosol and expose the dental team to an increased risk of infection though direct inhalation, contact with eyes and contact with contaminated work surfaces. 6,7 Dental aerosols therefore have the potential to provide a path for the transmission of COVID-19, 8,9 which may remain infectious for between two hours to nine days in a humid environment. 7 Research on the influenza virus has also demonstrated that the total viral copies are 8.8 times more numerous in particles <5 μm than in particles ≥5 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Data from our most realistic model (model 2, dye in mouth) produced reassuring results for distant contamination in open plan clinics. Several authors have previously discussed the dilution effect of the dental water spray on saliva [ 8 , 18 ]. Moderate contamination was detected within the AGP bay using model 2 and more modest contamination was seen in bays opposite where there is no barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The potential viral load of aerosol and splatter created during dental procedures is not known, and nor is any estimate of the dilution effect produced by the water irrigation from the instruments available. Similarly, the effect of mitigating measures such as suction and ventilation is not well understood or explored [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is a β-coronavirus, and similar to other respiratory pathogens, can be spread through droplets generated during talking, sneezing, and coughing. In addition, it can be transmitted by “infected” aerosols generated during medical or dental procedures [ 51 , 52 , 53 ]. The first step for SARS-CoV-2 infection is the binding to angiotensin-converting enzyme 2 (ACE2), a host cell receptor expressed in lung cells and multiple extrapulmonary tissues [ 54 , 55 ].…”
Section: Pathogenesis Of Covid-19mentioning
confidence: 99%